Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 1:
\(=\dfrac{15}{34}+\dfrac{19}{34}-1-\dfrac{15}{17}+\dfrac{1}{3}+\dfrac{3}{5}\)
\(=-\dfrac{15}{17}+\dfrac{14}{15}=\dfrac{13}{255}\)
Câu 2:
\(=\dfrac{5^4\cdot5^4\cdot2^8}{4^4\cdot6^4\cdot3^2\cdot5}=\dfrac{5^7}{6^4\cdot3^2}\)
\(\dfrac{15}{34}+\dfrac{7}{21}+\dfrac{19}{34}-1\dfrac{15}{17}+\dfrac{2}{3}\)
= \(\left(\dfrac{15}{34}+\dfrac{19}{34}\right)+\left(\dfrac{7}{21}+\dfrac{2}{3}\right)-1\dfrac{15}{17}\)
= \(1+\left(\dfrac{7}{21}+\dfrac{14}{21}\right)-1\dfrac{15}{17}\)
= \(1+1-1\dfrac{15}{17}\)
= \(2-1\dfrac{15}{17}\)
= \(\dfrac{2}{17}\)
`15/34+7/21+9/34-1 15/17+2/3`
`=(15/34+9/34)+(7/21+2/3)-32/17`
`=12/17+1-32/17`
`=(12/17-32/17)+1`
`=-20/17+1`
`=-3/17`
=(15/34+9/34-15/17)+(1/3+2/3)
=(24/34-15/17)+1
=-3/17+1
=14/17
\(A=\dfrac{15}{34}+\dfrac{1}{3}+\dfrac{9}{34}-\dfrac{32}{17}+\dfrac{2}{3}\)
\(A=\dfrac{15}{34}+\dfrac{1}{3}+\dfrac{9}{34}-\dfrac{64}{34}+\dfrac{2}{3}\)
\(A=\left(\dfrac{15}{34}+\dfrac{9}{34}-\dfrac{64}{34}\right)+\left(\dfrac{1}{3}+\dfrac{2}{3}\right)\)
\(A=\dfrac{40}{34}+1=2\dfrac{6}{34}\)
\(A=\dfrac{15}{34}+\dfrac{7}{21}+\dfrac{9}{34}-1\dfrac{15}{17}+\dfrac{2}{3}\)
\(=\dfrac{15}{34}+\dfrac{1}{3}+\dfrac{9}{34}-1\dfrac{15}{17}+\dfrac{2}{3}\)
\(=\left(\dfrac{15}{34}+\dfrac{9}{34}\right)+\left(\dfrac{1}{3}+\dfrac{2}{3}\right)-1\dfrac{15}{17}\)
\(=1+1-1\dfrac{15}{17}\)
\(=2-1\dfrac{15}{17}\)
\(=\dfrac{2}{17}\)
a) \(\left(7\dfrac{1}{3}-\dfrac{1}{3}\right):\dfrac{1}{7}\)
\(=\left(\dfrac{22}{3}-\dfrac{1}{3}\right):\dfrac{1}{7}\)
\(=7:\dfrac{1}{7}=7.7=49\)
b) \(\dfrac{-1}{3}.\left(\dfrac{-15}{17}\right).\dfrac{34}{45}\)
\(=\dfrac{-1}{3}.\left(\dfrac{-15}{17}.\dfrac{34}{45}\right)\)
\(=\dfrac{-1}{3}.\dfrac{-2}{3}=\dfrac{2}{9}\)
c)\(\dfrac{1}{2}.\dfrac{6}{5}-\dfrac{1}{5}.\dfrac{1}{2}\)
\(=\dfrac{1}{2}.\left(\dfrac{6}{5}-\dfrac{1}{5}\right)\)
\(=\dfrac{1}{2}.1\)
\(=\dfrac{1}{2}\)
c) \(\frac{1}{2}.\frac{6}{5} - \frac{1}{5}.\frac{1}{2}\)
\(= \frac{1}{2}\left. ( \frac{6}{5} - \frac{1}{5}\right )\)
= \(\frac{1}{2}.1 = \frac{1}{2}\)
\(\left(-\dfrac{1}{3}\right)\times\left(-\dfrac{15}{17}\right)\times\dfrac{34}{45}\)
\(=\dfrac{15}{51}\times\dfrac{34}{45}\)
\(=\dfrac{510}{2295}\)